Tingkat Kepercayaan Anggota Terhadap Perkembangan Sistem Informasi Akuntansi Koperasi - Tama Wijaya, I Made Ari (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze cooperative members’ trust in the development of accounting information systems in East Denpasar District. The research variables include the use of accounting information systems, users’ technical skills, and employees’ training levels. A quantitative approach was employed using purposive sampling on 66 cooperative members, and data were analyzed with multiple linear regression through SPSS 27. The results indicate that the use of accounting information systems has a positive and significant effect on members’ trust in cooperatives. However, users’ technical skills and employee training levels show no significant impact on members’ trust. These findings suggest that members’ trust is primarily influenced by the implementation of accounting information systems rather than internal managerial factors. The study implies that cooperatives should enhance the application of digital accounting information systems to strengthen transparency and trust among members.